Pembinaan Kelompok Tani Pengendalian Hama Tikus Dengan Metode Gropyokan Di Desa Sidowaluyo Kecamatan Sidomulyo - Safitri, Anggun; Sepri YH, Aryan Ari; Pardani, Nanda (Journal Of Human And Education (JAHE), 2024)
Farmers in Sidowaluyo Village, South Lampung, face a serious problem in the form of rice field rat (Rattus argentiventer) pest attacks that cause significant damage and potential crop failure. This coaching applies the gropyokan method, namely mutual cooperation pest eradication, as a solution to control rat pests that damage farmers' rice crops in Sidowaluyo. Before the gropyokan implementation, a focus group discussion or Forum Group Discussion (FGD) was held, where the purpose of this FGD was to increase understanding and change the perception of the community, especially farmers, regarding this problem. This FGD was conducted twice, with the aim not only to increase farmers' understanding regarding controlling this rat pest, but also to be more effective in finding solutions that are appropriate to land conditions and creating effective strategies in controlling this rat pest. The results of the FGD gave rise to an agreement to use traditional and environmentally friendly methods. Pest control is carried out in rice fields affected or attacked by rat pests, by combining gropyokan and composting using sulfur in areas that are difficult to access such as embankments or dunes on the edge of toll roads. The strategy in implementing this control is formed by team leaders to lead the group activities in each stretch or path. The success of this effort is shown by the number of mice caught or killed, and is expected to be an example and increase motivation for other farmers in overcoming rice field mouse attacks.